Orthopedic sports medicine principles and practice - Margheritini, Fabrizio; Rossi, Roberto (Springer eBooks., 2011)
Aim of this book is to give an update on the main issues in sports traumatology and orthopedics, involving different body sections. Exploring the most important aspects of sports medicine - from anatomy to normal movements description, from diagnosis to sports injuries treatment, from conservative to surgical treatments - it gives a global overview of the field, describing also diagnostic tools recently introduced in this field, such as hip arthroscopy, and taking into consideration related areas like nutrition, prevention, training and rehabilitation. The single chapters deal with relevant pr.